EFFECT OF INCENTIVES ON EMPLOYEES’ PERFORMANCE AT BINGHAM UNIVERSITY, KARU, NASARAWA STATE - Tunde Atotileto, Victor; James Dauda Mshelia, James; Naomi, Paul; Mercy Oladimeji, Oluwadamilola; Danladi, Kefas (African Journal of Social and Behavioural Sciences, 2024)
The mismanagement of incentives given to employees in the contemporary workplace environment has never received urgent concern, as is the case today, considering the line of economic issues affecting the performance of employees. This study examined the effect of incentives on employee performance at Bingham University, Karu, Nasarawa State, Nigeria. The specific objectives were to assess the effects of promotions and bonuses on employee performance at Bingham University, Karu, Nasarawa State, Nigeria. The study adopted a survey research design, and the data were collected through questionnaires and analysed via Excel for data coding, descriptive statistics, correlation and multiple linear regression techniques. A total of 1076 staff constituted the population of the study. The Taro Yammane sampling method was used to obtain a reliable sample size of 294 staff of Bingham University, Karu, Nasarawa state, Nigeria. The findings of the study show that bonuses have positive but insignificant effects on employee performance at Bingham University, Karu, Nasarawa State, Nigeria, whereas promotions have positive and significant effects on employee performance at Bingham University, Karu, Nasarawa State, Nigeria. The study recommends that bonuses such as overtime pay for working beyond the usual working hours to nonteaching staff, specifically staff working in sections where the workload is much as long as the employment of more staff seems impossible. In addition, to the teaching staff, bonuses such as allowances for the running of additional programmes, mobile data for connecting to the internet in the case of online lectures, as well as those holding temporary positions such as exam officers, etc., should be provided. The management of Bingham University should frequently check the activities of the human resource or promotion committee to ensure that the personal interest of any member of the promotion unit does not hinder the progress or promotion of qualified employees, as this may cause demoralization of talent, thereby resulting in turnover.